1965
DOI: 10.2307/1126465
|View full text |Cite
|
Sign up to set email alerts
|

Children's Reports of Parental Behavior: An Inventory

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. Wiley and Society for Research in Child Development are collaborating with JSTOR to digitize, preserve and extend access to Child Development. The development of a set of scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
564
1
21

Year Published

2002
2002
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,354 publications
(591 citation statements)
references
References 8 publications
5
564
1
21
Order By: Relevance
“…The parenting quality composite includes four variables: two subscales from the Children’s Report of Parental Behavior Inventory (CRPBI (37, 38), rejection (10 items; alpha=.72) and consistent discipline (8 items; alpha= .83) and two subscales of the Conflict Tactics Scale – Parent Child version II (CTSPC-II) (39), non-violent discipline (4 items; alpha = .76) and psychological aggression (5 items; alpha .77).…”
Section: Methodsmentioning
confidence: 99%
“…The parenting quality composite includes four variables: two subscales from the Children’s Report of Parental Behavior Inventory (CRPBI (37, 38), rejection (10 items; alpha=.72) and consistent discipline (8 items; alpha= .83) and two subscales of the Conflict Tactics Scale – Parent Child version II (CTSPC-II) (39), non-violent discipline (4 items; alpha = .76) and psychological aggression (5 items; alpha .77).…”
Section: Methodsmentioning
confidence: 99%
“…Given that parental behavior, such as checking children's homework, may be perceived by the child as either supportive or intrusive, we considered the students' response instead of the parents' response or any other objective measure. In fact, previous research has shown that children's interpretations of parental behavior are more strongly related to their development than are parents' actual behaviors (Grolnick, Ryan, & Deci, 1991;Grolnick & Slowiaczek, 1994;Hoover-Dempsey et al, 2005;Schaefer, 1965). Hence, children's reports have been commonly used as indicators of parenting quality (Schaefer, 1965).…”
Section: The Present Studymentioning
confidence: 99%
“…Since then, many parental factors have been studied and associated with children's psychological adjustment. Baumrind (1966Baumrind ( , 1991Baumrind ( , 2005 suggests two orthogonal dimensions, high-low warmth and high-low control, and Schaefer (1965) suggests a similar pair (warmth-hostility and detachment-involvement). Rohner (1986Rohner ( , 1999 focuses on the dimension of parental acceptance-rejection in addition to parental control.…”
Section: Introductionmentioning
confidence: 99%